Competition as a Tool for Achieving Sustainable Development in Rail Transport - Jarecki, Stefan Akira (Studia Ecologiae et Bioethicae, 2021)
Railways are crucial for the achievement of sustainable transport development. National, along with EU legislators, recognised that, for environmental reasons, railways should have a high share in modal split. According to the EU, competition in rail service markets will encourage railway operators to become more responsive to customer needs, improve the quality of their services, and their cost-effectiveness and thus, they will strengthen the competitive position of railways. Therefore, the EU’s law duly opened up railway service markets to competition. The aim of this article is to analyse whether it is sufficient to achieve sustainable transport development. I shall focus on the existing law regulations, their clarification (interpretation), and systematisation. Therefore, the character of my research will be generally dogmatic. In my opinion, competition in rail transport can contribute to its increase, however, it should be guaranteed that the costs of introducing competition would not exceed its benefits. Moreover, to achieve the goals of national and EU policy in the area of sustainable transport development, it is necessary to ensure the equal conditions of competition between rail and less environmentally-friendly modes of transport, especially road transport (in particular, with regard to fees for the use of infrastructure).